The introduction of clinical genetic testing in Ethiopia: Experiences and lessons learned. Issue 10 (24th June 2021) - Quinonez, Shane C.; Terefework, Zewdu
Abstract: Limited data are available on genetic testing laboratories in low‐ and middle‐income countries including those in sub‐Saharan Africa (SSA). To characterize the need for genetic testing in SSA we describe the experience of MRC‐ET Advanced Laboratory, a genetic testing laboratory in Ethiopia. Test results were analyzed based on indication(s) for testing, referral category, and diagnostic yield. A total of 1311 tests were run using the full MRC‐Holland catalogue of Multiplex‐Ligation Probe Amplification assays. Of all samples, 77% were postnatal samples, 15% products of conception (POC), and 8% amniotic samples. Of postnatal samples, the most common testing categories were multiple congenital anomalies (32%), disorders of sex development (17%), and Obstetrics/Gynecology (16%). Forty‐three percent of postnatal samples were diagnostic, 11% were variants of uncertain significance (VUS), and 46% were normal with Trisomy 21 the most common diagnosis. Of POC samples, 10% were diagnostic, 34% revealed VUSs, and 55% were normal with Trisomy 18 the most common diagnosis. Of amniotic samples 17.5% were diagnostic, 3% revealed VUSs, and 79% were normal with Trisomy 18 the most common diagnosis. There is increasing demand for genetic testing in Ethiopia. Diagnostic genetic testing in SSA deserves increased attention as testing platforms become more affordable.